2021
DOI: 10.3390/jcm10122647
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 and MMP-9 Polymorphisms and Preeclampsia Risk in Tunisian Arabs: A Case-Control Study

Abstract: The abnormal production of matrix metalloproteinases (MMPs), especially MMP-9 and MMP-2, plays a pivotal role in hypertensive disorders of pregnancy, and as such, can influence the development of preeclampsia. These alterations may result from functional genetic polymorphisms in the promoter region of MMP-9 and MMP-2 genes, which modify MMP-9 and MMP-2 expression. We investigated the association of MMP-9 polymorphism rs3918242 (-1562 C>T) and MMP-2 polymorphism rs2285053 (-735 C>T) with the risk of preec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(64 reference statements)
0
7
0
2
Order By: Relevance
“…to differential CREM expression in RA vs. controls but act as RA phenotype modifiers Rheumatoid arthritis medication was not a causative factor for the observed differential expression between RA and controls; hence, we pursued other possible reasons. As genetic factors constitute a well-established regulatory mechanism of gene expression, 12 we investigated whether different CREM genotype distributions account for the higher CREM expression found in RA. We first retrieved all CREM variants studied in the literature (Table 1), [23][24][25][26][27][28][29][30][31] two of which (rs11592989 and rs12770114) are monomorphic in CHB (Table 1).…”
Section: Crem Variants Do Not Contributementioning
confidence: 99%
See 1 more Smart Citation
“…to differential CREM expression in RA vs. controls but act as RA phenotype modifiers Rheumatoid arthritis medication was not a causative factor for the observed differential expression between RA and controls; hence, we pursued other possible reasons. As genetic factors constitute a well-established regulatory mechanism of gene expression, 12 we investigated whether different CREM genotype distributions account for the higher CREM expression found in RA. We first retrieved all CREM variants studied in the literature (Table 1), [23][24][25][26][27][28][29][30][31] two of which (rs11592989 and rs12770114) are monomorphic in CHB (Table 1).…”
Section: Crem Variants Do Not Contributementioning
confidence: 99%
“…Furthermore, if CREM is differentially expressed in RA, the exact molecular events contributing to dysregulated CREM expression are incompletely understood. Genetic and epigenetic determinants of gene expression are well characterized, 12,13 but it is unclear whether differential CREM expression in RA can be attributed to CREM variants and CREM methylation. Indeed, no studies to date have examined these possibilities.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis performed in 2018, the only detected correlation with PE risk was 4G/5G polymorphism of plasminogen activator inhibitor 1 (PAI-1) [ 88 , 89 ]. Gannoun et al investigated genetic polymorphisms in the promoter region of matrix metalloproteinases 9 and 2 (MMP-9 and -2) in a Tunisian Arab population and revealed that the MMP-9 rs3918242 (-562 C > T) variant is related to increased MMP-9 production and is a risk factor for PE [ 90 ]. In a recently published meta-analysis, Liu et al identified transforming growth factor-beta 1(TGF-β1) rs800469 variant as a possible risk factor for PE in Asian population [ 91 ].…”
Section: Fetal Growth Restriction and Preeclampsia As A Maternal Factormentioning
confidence: 99%
“…Moreover, previous work by our group has demonstrated an association between two variants of PPARγ (Pro12Ala and C1431T) and gestational diabetes [22]. Even though multiple studies have suggested that SNPs in various genes increase the risk of preeclampsia [23][24][25], the association between SNPs of PPARγ and the risk of preeclampsia has been poorly investigated.…”
Section: Introductionmentioning
confidence: 97%